Prevalence and Diversity of Endosymbionts in Cassava Whiteflies (Hemiptera: Aleyrodidae) From Colombia - Gómez-Díaz, Juan Sebastián (J Insect Sci, 2019)
Whiteflies cause huge economic losses for cassava (Manihot esculenta Crantz) cultivation. Damage can be caused directly when the insects feed on the phloem and/or indirectly by the transmission of viruses. It has been found that whiteflies maintain a close relationship with some endosymbiotic bacteria and that this interaction produces different effects on host biology and can also facilitate viral transmission. This study aimed to characterize the diversity of secondary endosymbionts (SE) present in whiteflies associated with cassava. Whitefly adults and nymphs were collected from cassava crops at nine locations in Southwestern Colombia. Molecular identification of insects and endosymbionts was carried out using specific mtCOI, wsp, 23s rRNA, and 16s rRNA primers. Phylogenetic trees were constructed from these sequences, both for whitefly species and the endosymbionts found. In addition, morphological identification of whitefly species was made using last instar nymphs. Molecular and morphological evaluation revealed that the most abundant whitefly species was Trialeurodes variabilis (Quaintance) followed by Aleurotrachelus socialis Bondar and Bemisia tuberculata Bondar. One hundred percent of the individuals contained the primary endosymbiont Portiera. The SE Rickettsia, Hamiltonella, Wolbachia, and Fritschea were not detected in the samples tested. Prevalence of Cardinium and Arsenophonus were variable at each locality, Cardinium being most prevalent in A. socialis adults. This study is the first report on the presence of Cardinium and Arsenophonus in A. socialis and T. variabilis. It is also the first report of endosymbiotic diversity in whiteflies associated with cassava in Colombia.